Significance of Follow-up of Patients on Anti-Tuberculosis Treatment and Defaulter Tracing: Bangladesh Perspective - Khan, Sonia Islam (Bangladesh Journal of Infectious Diseases, 2022)
Abstract not available Bangladesh Journal of Infectious Diseases December 2021;8(2):55-56